GENDER AND LINGUISTIC REPRESENTATION IN ROHINTON MISTRY’S NOVELS - Bhadoo, Neha; Dubey, Neeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article delves into the nuanced portrayal of gender and linguistic representation in Rohinton Mistry’s acclaimed novels, particularly "Such a Long Journey" and "A Fine Balance." Mistry, a prominent figure in contemporary literature, is known for his intricate exploration of the Parsi community in India, a focus that allows him to engage deeply with issues of identity, culture, and societal norms. This study examines how Mistry constructs gender identities and employs linguistic diversity as tools for both narrative development and social critique. The analysis highlights Mistry’s depiction of gender roles, revealing a complex interplay between traditional expectations and individual agency. Female characters in Mistry’s works, such as Dilnavaz and Dina Dalal, are portrayed within the confines of conventional gender roles but also exhibit significant resilience and strength, challenging patriarchal structures in subtle yet profound ways. These characters’ experiences underscore the broader societal constraints faced by women and their strategies for navigating and sometimes subverting these limitations. Linguistically, Mistry’s novels are characterized by a rich tapestry of languages, including Gujarati, Hindi, Marathi, and English. This multilingual approach reflects the diverse linguistic landscape of India and serves as a critical commentary on social stratification and cultural identity. The use of English, in particular, is often associated with social status and colonial legacy, highlighting issues of power and privilege. Mistry’s nuanced use of language not only enhances the authenticity of his characters and settings but also deepens the thematic exploration of identity and resistance. By focusing on these elements, the article contributes to a broader understanding of how literature can reflect and critique societal norms, particularly in postcolonial contexts. Mistry’s work, with its emphasis on marginalized voices and cultural diversity, offers a valuable lens through which to examine the complexities of gender and language in shaping individual and collective identities. This study underscores the significance of Mistry’s novels in the ongoing discourse on cultural identity, social justice, and literary expression.